Gir Calves Growth Performance, Feed Intake and Micro-Climate Variation under Different Housing Modification System during Winter Season - Jat, Maya; Jat, Ram Prasad; Bhateshwar, Vinod; Paswan, Vinod Kumar; Nehra, Hanuman Lal (Indian Journal of Dairy Science, 2021)
The better scientific management of the calves during the growth phase ensures an optimal body growth rate and efficient feed conversion efficiency and has thus has a direct effect on the life time production and reproductive performance of dairy animals. This study investigated the Gir calves growth performance, feed intake and micro-climate variation under different housing modification system during winter season. Twenty-four healthy Gir calves of twelve months of age were randomly divided into three homogenous modified housing groups containing with eight calves in each group. Group GC-1: conventional barn (during night) + open paddock (during day), GC-2: conventional barn + rubber mat and GC-3: loose house + curtains. The concentrate supplements given 1.5 kg/calve/day as pellet feed, green lucerne (Medicago sativa) 2.5 kg/calve/day and wheat straw (Triticum aestivum) ad lib as dry fodder. During the statistical analysis, the mean minimum morning temperature (P<0.05) was higher in GC-2 (11.81oC) over than GC-1 (10.64oC) and GC-3 (11.27oC) and the maximum morning temperature was significantly higher in GC-3 (22.97oC), which is above than groups GC-1 (22.21oC) and GC-2 (22.39oC). However, the mean value of the minimum evening temperature was significantly highest into GC-2 (12.40oC) followed by GC-3 (11.86oC) and GC-1 (11.67oC) and the maximum evening temperature was highest in GC-1 (24.95oC) followed by GC-3 (23.98oC) and GC-2 (23.54oC). The average mean both relative humidity (RH) percent and temperature humidity index (THI) along with morning and evening times was (P<0.05) higher in GC-1 than GC-2 and GC-3 groups. However, total dry matter intake, voluntary water intake and feed efficiency were significantly higher in the GC-1 group compared to the calves in the GC-2 and GC-3 groups. The monthly total average body weight gain of the claves was significantly (P<0.05) highest in group GC-1 (145.62 kg) followed by GC-2 (142.84) and GC-3 (142.35) groups. However, group GC-1 achieved the significantly (530.90 g/day) average daily weight gain followed by GC-2 (472.05 g/day) and GC-3 (449.88 g/day). It was concluded that the housing modification system can be effectively used to improve the growth performance, feed intake and sheds micro-climate of Gir calves during the winter season.